(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The presentation of an information system, for example, Enterprise Resource Planning (ERP) system in an organization carries with it changes on how clients work. An ERP system cuts over the distinctive functional units of an organization and in this manner if not appropriately oversaw amid its usage may prompt obstruction from the clients. The various surges of research on ERP systems have predominantly been on ERP selection, achievement measurement, and basic achievement factors (CSFs). There is a lack of concentrates on client participation and the commitment of clients towards the effective execution of ERP systems. This paper audits writing on ERP usage with a point of structure a case for including users in this execution.